The Role of Medication Data to Enhance the Prediction of Alzheimer's Progression Using Machine Learning. (22nd September 2021) - El-Sappagh, Shaker; Abuhmed, Tamer; Alouffi, Bader; Sahal, Radhya; Abdelhade, Naglaa; Saleh, Hager
Abstract : Early detection of Alzheimer's disease (AD) progression is crucial for proper disease management. Most studies concentrate on neuroimaging data analysis of baseline visits only. They ignore the fact that AD is a chronic disease and patient's data are naturally longitudinal. In addition, there are no studies that examine the effect of dementia medicines on the behavior of the disease. In this paper, we propose a machine learning-based architecture for early progression detection of AD based on multimodal data of AD drugs and cognitive scores data. We compare the performance of five popular machine learning techniques including support vector machine, random forest, logistic regression, decision tree, and K-nearest neighbor to predict AD progression after 2.5 years. Extensive experiments are performed using an ADNI dataset of 1036 subjects. The cross-validation performance of most algorithms has been improved by fusing the drugs and cognitive scores data. The results indicate the important role of patient's taken drugs on the progression of AD disease.